1986
DOI: 10.1063/1.336964
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of shallow-donor levels in GaAs

Abstract: Shallow-donor levels due to Si, Ge, Sn, S, Se, and Te in GaAs are neutralized by association with atomic hydrogen; Si and Te donors in AlGaAs have also been shown to be neutralized. In contrast, the shallow acceptors Be, Mg, Zn, and Cd in GaAs are relatively unaffected by hydrogenation. The activation energy for recovery of the donor electrical activity is around 2.1 e V for each of the species, but varies as the strength of an isolated hydrogen-donor species bond. The neutralization depth of the donors is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…2). Such low dissociation energy is close to the dissociation energy of other H-donor complexes [6], of the order of 2 eV. For higher temperature the experimental points deviate substantially from the theoretical curve described by (2).…”
mentioning
confidence: 71%
“…2). Such low dissociation energy is close to the dissociation energy of other H-donor complexes [6], of the order of 2 eV. For higher temperature the experimental points deviate substantially from the theoretical curve described by (2).…”
mentioning
confidence: 71%
“…[16][17][18][19][20] Since it is difficult to measure N O and N directly, Eq. where N O Ј and NЈ are the concentrations of unpassivated defects before and after annealing, respectively, which dictate the carrier lifetime.…”
Section: B Understanding and Kinetics Of The Hydrogen-defect Dissocimentioning
confidence: 99%
“…Therefore hydrogenation is carried out either in hydrogen plasma or in atomic hydrogen ͑AH͒. Analysis of the data available in the literature has shown that hydrogenation of GaAs samples in the plasma of an rf discharge at hydrogen pressures p у10-100 Pa [10][11][12] and pϭ0.1 Pa, 13 like in AH flow at p ϭ10 Ϫ2 Pa, 7,14 gives rise to semiconductor structures with similar electrophysical characteristics. This suggests that the penetration of AH into semiconductors depends not as much on the partial pressure of AH as on some other more essential factors.…”
Section: Introductionmentioning
confidence: 97%